Reporting guidelines for realist evaluations seek to improve clarity and transparency - Welch, Vivian A; Tricco, Andrea C (Université d'Ottawa | University of Ottawa, 2016)
Abstract An increasing number of realist evaluations are being conducted from a wide range of disciplinary perspectives and with diverse, fit-for-purpose methods. This commentary discusses the recent BMC Medicine publication of RAMESES II reporting guidelines for realist evaluations. Knowledge users such as program implementers and decision-makers will benefit from the increased transparency of reporting and interpretation in light of the totality of evidence encouraged by this guidance. It is hoped that these reporting guidelines will eventually lead to improved knowledge synthesis and contribute to the cumulative science regarding realist evaluation. Please see related article: https://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-016-0643-1